The Determinants of the Attractiveness of an Industry: An Extension of the Porter's Five-Forces Framework (Global Journal of Management and Business Research, 2022)
Abstract not found
Keywords: industry attractiveness; competitive forces; optimal industry capital structure; power of lenders